Role of pentahedrally coordinated titanium in titanium silicalite-1 in propene epoxidation1. Issue 23 (13th March 2015) - Zuo, Yi; Liu, Min; Zhang, Ting; Hong, Luwei; Guo, Xinwen; Song, Chunshan; Chen, Yongsheng; Zhu, Pengyu; Jaye, Cherno; Fischer, Daniel
<x xml:space="preserve">Abstract</x> A new pentahedrally coordinated Ti was discovered in TS-1 and showed a higher catalytic activity than the tetrahedrally coordinated one.